Anti-influenza a virus antibodies in Tayassuidae from commercial rearing farms in Brazil - Baraldi, Thaís Gasparini [UNESP]; Almeida, Henrique Meiroz de Souza [UNESP]; de Morais, Amanda Bonalume Cordeiro [UNESP]; Storino, Gabriel Yuri [UNESP]; Montassier, Hélio José [UNESP]; Motta, Rodrigo Garcia; Ribeiro, Márcio Garcia [UNESP]; de Oliveira, Luís Guilherme [UNESP] (FapUNIFESP (SciELO), 2019)
Family Tayassuidae in the suborder Suina include two species of peccaries in Brazil: the white-lipped peccary (Tayassu pecari) and the collared peccary (Pecari tajacu). These animals share common pathogens with domestic swine (Sus scrofa); however, their role as potential carrier remains unclear. This study focused on detecting the prevalence of influenza A antibodies in Tayassu pecari and Pecari tajacu from commercial rearing farms from two states in Brazil. A set of 50 blood samples from Pecari tajacu and 55 from Tayassu pecari were analyzed using a commercial indirect ELISA in order to investigate anti influenza A antibodies. Pecari tajacu samples presented 22% (11/50) of seropositivity for the virus. Serological surveillance is an important tool to identify the presence and the spread of the influenza virus in feral pigs.
Detecção de anticorpos contra vírus influenza a em tayassuidae de criações comerciais no Brasil
Keywords: Antibodies; Influenza; Peccaries